The Limnological Effects of River Lesser-Zab on Tigris River, Iraq (Baghdad Science Journal, 2007)
The present study included the physico-chemical parameters of Lesser-Zab river and its effects on Tigris river. Monthly water samples were taken from the two rivers during January to October 1999.There were no signifcant difference in water temperatures. Both rivers were fresh to oligohalin, alkaline and very hard. Close values were determined in total suspended solids in both rivers with little increasing during rainfall period and high discharge. Water was well areated and over saturation was recorded in several occasions. Dissolved oxygen values of Tigris river were influenced by Lesser-Zab. Cations were more dominant than anions in both rivers. In Lesser-Zab, the anions were increased during spring season and declined in summer which their values influenced in Tigris river. The concentration of plant nutrients (NO2,NO3,PO4 and SiO2) were fluctuated during the study period in Lesser-Zab and their effects were cleared on Tigris river.N:P ratio values were indicated the deficiency of nitrogen in both rivers.